Modeling the Pāṇinian System of Sanskrit Grammar - Mishra, Anand (Heidelberg University Publishing (heiUP), 2019)
The present work is a study of the Aṣṭādhyāyī of Pāṇini from a new perspective. It attempts to explore the Pāṇinian system of Sanskrit grammar from a formal point of view and investigate the possibilities of representing it in a logical, explicit and consistent manner. It puts forward an appropriate framework for such a representation. Differing from the formulation of Aṣṭādhyāyī, which is composed in an artificial yet natural language and is meant to be employed by individuals who are acquainted both with the Sanskrit language and the techniques of grammar, the present rendering aims for a non-verbal representation in terms of mathematical categories and logical relations which can be implemented in an algorithmic manner. The formal framework suggested in this work would facilitate adequate tools for postulating and evaluating hypotheses about the grammatical system. Moreover, it would furnish the basis for a computer implementation of the grammar. Both these aspects are objects of enquiry in the field of theoretical studies on Pāṇini as well as the emerging discipline of Sanskrit computational linguistics. This book takes on the ground-work in these areas.